Microplastic exposure under future oceanic conditions further threatens an endangered coral, Acropora cervicornis - Sugierski, Sharla; Campbell, Chad; Hall, Emily R.; McLean, Matthew; Fogarty, Nicole D. (Frontiers in Marine Science, 2025)
Microplastic pollution is ubiquitous in the oceans. However, little is known about the physiological impact of microplastics on corals, particularly under predicted future ocean conditions. This study investigated the individual impacts of microplastic exposure (MP) and predicted future ocean conditions [ocean acidification and warming (OAW)] as well as the combination of these stressors (OAW+MP) on the growth and physiology of Acropora cervicornis, a threatened Caribbean coral and its associated symbiont, Symbiodiniaceae. After 22 days, the OAW+MP treatment resulted in more pronounced physiological changes than either stressor individually or the control. OAW conditions alone had minimal impacts, despite A. cervicornis generally being sensitive to thermal stress. The OAW+MP treatment and the MP treatment also disrupted the host-symbiont relationship evidenced by the higher symbiont densities relative to the control and the OAW treatments. Additionally, the OAW+MP treatment resulted in lower chlorophyll a per symbiont cell. Microplastic handling is energetically costly, possibly leading to changes in host-symbiont signaling. Photosynthetic efficiency was only marginally lower in the OAW+MP treatment, and values did not indicate photosystem damage. Negative host health impacts were found with the OAW+MP treatment exhibiting lower skeletal growth compared to the control and lower host protein concentrations compared to the OAW treatment. These results indicate that although short term microplastic exposure alone may not pose a significant threat to coral health, when adding additional stressors, it can further threaten the health and recovery of this already vulnerable species.